Stillbirth in Khayelitsha Hospital, South Africa: Women's Experiences of Care. (1st March 2022) - Lappeman, Maura; Swartz, Leslie
Abstract : In this study we explore the hospital care experience of women following stillbirths in an impoverished urban setting in the Western Cape Province of South Africa. A qualitative research methodology was used with the collection of primary data using the Free Association Narrative Interview Method with 10 women who experienced stillbirths at a government hospital. The study found that the women generally felt well looked after medically, but also felt an emotional disconnect from, and a need to be seen by, the medical staff. A stillbirth can confront both the woman and the clinician with their own helplessness. Without attention to the emotional needs of the staff, who seemed to be offering optimal care within their capacity, it is unlikely that the staff will be able to provide fully accessible emotional care for the women. The stories told to us by our participants suggest that more expenditure on the emotional needs of caregivers in the health system may contribute to a more emotionally accessible, sustainable workforce.